Anatomy of the splenic artery: what does the surgeon need to know? - MORAES,DAVID MATHEUS VIANA DE (2022)
ABSTRACT Objective: to determine the prevalence and describe the main morphological and metric variations of the splenic artery in terms of its origin, path and polar and terminal branches. Methods: cross-sectional study, carried out at Hospital de Clínicas between July and November 2020. Computed tomography scans were analyzed with intravenous contrast of the patients seen at the Radiology and Diagnostic Imaging Service. The findings were categorized as to origin, path and splenic ramifications. Results: 1,235 patients were evaluated. As for the origin, the splenic artery appears in the celiac trunk in 99.11% of the individuals. Of these, 5.95% have a bifurcated celiac pattern, 92.17% trifurcated and 1.88% tetrafurcated. The mean arterial diameter was 5.92mm (±1.2), the highest one being in white men. As for the path, the splenic artery was unique in the entire sample. The suprapancreatic course was found in 75.63% of the individuals, with a higher occurrence in women, 78.87% (p<0.001). The terminal splitting pattern of the splenic artery was characterized by the bifurcated type (95.47%). The terminal branches seen most frequently were those with three arteries (34.90%) and most individuals did not have polar branches. Conclusion: the splenic artery presents a highly variable pattern of origin and its average caliber is influenced by sex and color. The suprapancreatic path was the most characteristic and predominant in females. The bifurcated pattern of final division, with three terminal branches and the absence of polar arteries, occurs more frequently.